Human leukocyte antigen polymorphism in chronic and aggressive periodontitis among Caucasians: a meta-analysis - Jamal M. Stein (Blackwell Synergy, 2008)
Aim: Multiple studies have reported associations between periodontitis and particular human leukocyte antigens (HLA). Because associations are inconsistent, we conducted a systematic literature review and a meta-analysis focusing on Caucasian case–control studies. Material and Methods: A literature search reporting on the distribution of HLA class I and II phenotypes in Caucasian patients with chronic periodontitis (CP) and aggressive periodontitis (AP) was performed. Data sources included electronic databases and bibliographies of published articles. Screening and data abstraction were conducted independently by different reviewers. Results: Out of 174 publications, 12 studies were considered to be suitable for metaanalysis. In patients with CP, no significant HLA associations were found. Patients with AP showed a positive association with HLA-A9 [odds ratio52.59 (95% confidence interval 1.36–4.83), p50.004] and HLA-B15 [1.90 (1.15–3.16), p50.01] as well as a negative association with HLA-A2 [0.72 (0.56–0.94), p50.01] and -B5 [0.49 (0.30–0.79), p50.004]. On grouping all patients into one periodontitis group (AP1CP), the same deviations were confirmed with higher statistical significance. For HLA-A9 and -B15, significant heterogeneity was found between the studies. No significant associations were found with HLA class II antigens. Conclusions: HLA-A9 and -B15 seem to represent susceptibility factors for AP whereas HLA-A2 and -B5 are potential protective factors against periodontitis among Caucasians.